The significance of epistemic integration between philosophy and medicine among Medieval Islamic Philosophers: Ibn Rushd of Cordoba as a model (d. 595 AH/1198 CE) - KHODIR, Babaouamer; KAABOUCHE, Ahmed; DRISSI, Douaa (The International tax journal, 2026)
Epistemic integration constitutes an intellectual characteristic and a methodological tool that distinguished many Muslim scholars in the medieval period, including philosophers, theologians, jurists, physicians, and linguists. The distinctive feature of epistemic integration among medieval Islamic philosophers is grounded in two principal factors. The first lies in their theory of knowledge, which is based on diverse yet complementary sources: revealed divine scripture, the observable cosmos, reason, and sense perception. The second factor is their profound conviction in the proximity and interpenetration of the sciences, coupled with their keen concern for classifying and systematising them and for elucidating their relationships. Abū al-Walīd Ibn Rushd of Cordoba stands as a pioneering figure and an eminent philosopher in embodying the theory of epistemic integration. He succeeded, with rigour and methodological clarity, in forging strong connections between diverse fields of knowledge such as jurisprudence, philosophy, medicine, and ethics, thereby rendering him a model from which contemporary thought may benefit. Linking scientific progress in medicine and biological research to ethics, religion, philosophy, and legislation ensures the attainment of individual well-being and the preservation of human dignity.